2021
DOI: 10.3390/ijerph182010715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opposite Tooth Condition on Marginal Bone Loss around Submerged Dental Implants: A Retrospective Study with a 3-Year Follow-Up

Abstract: Background: The objective of this study was to evaluate the effects of opposite tooth conditions on change in marginal bone level (MBL) around submerged dental implants. Materials and methods: The study included healthy patients with one or two implants. Structures opposite implants were either natural teeth (NT) or fixed restorations (FRs). MBLs were measured on digital periapical radiographs at the mesial and distal aspects of each implant. Results: Sixty implants were inserted by the 3-year follow-up. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…Research conducted by Dorj et al (2021) showed a statistically significant difference in bone resorption in the period after 3 years, so one could conclude that duration of wearing a work affects bone change, which is in contrast to this research ( 16 ).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Research conducted by Dorj et al (2021) showed a statistically significant difference in bone resorption in the period after 3 years, so one could conclude that duration of wearing a work affects bone change, which is in contrast to this research ( 16 ).…”
Section: Discussioncontrasting
confidence: 84%
“…Likewise, in this study, the influence of the state of the opposite jaw on the change in bone height was also not proven. In contrast to this, in the study conducted by Dorj et al (2021), it was found that a statistically significant difference in bone change, depending on the antagonist, exists and is greater in the case of metal-ceramic as the antagonist ( 16 ).…”
Section: Discussionmentioning
confidence: 83%
“…These opposing conditions results were in agreement with the previously published study. Authors found 0.30 mm of MBL for the natural teeth group and 0.53 mm of MBL for the fixed restoration group after 36-month loading [ 47 ]. Although the level of bone loss was slightly higher in the present study, lower marginal bone loss noted in the natural teeth group when compared with the dental prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement method was based on a previous study [ 26 ] in which both the mesial and distal MBLs were measured from the fixture platform to the alveolar ridge.…”
Section: Methodsmentioning
confidence: 99%
“…After taking baseline radiographs, follow-up radiographs should be taken annually thereafter [ 25 ]. The measurement method involving measuring the distance of the mesial and distal MBLs from the fixture platform to the alveolar ridge was commonly used in previous studies [ 26 ].…”
Section: Introductionmentioning
confidence: 99%